Serum Total Testosterone Concentrations in the US Household Population from the NHANES 2011–2012 Study Population. (6th January 2020) - Vesper, Hubert W; Wang, Yuesong; Vidal, Meghan; Botelho, Julianne Cook; Caudill, Samuel P
Abstract: BACKGROUND: Limited information is available about testosterone concentrations representative of the general US population, especially children, women, and non-Hispanic Asians. METHODS: We obtained nationally representative data for total testosterone (totalT), measured with standardized LC-MS/MS, for the US population age 6 years and older from the 2011–2012 National Health and Nutrition Examination Survey (NHANES). We analyzed 6746 serum samples and calculated the geometric means, distribution percentiles, and covariate-adjusted geometric means by age, sex, and race/ethnicity. RESULTS: The 10th–90th percentiles of totalT values in adults (≥20 years) was 150–698 ng/dL (5.20–24.2 nmol/L) in men, 7.1–49.8 ng/dL (0.25–1.73 nmol/L) in women, and 1.0–9.5 ng/dL (0.04–0.33 nmol/L) in children (6–10 years old). Differences among race/ethnic groups existed in children and men: covariate-adjusted totalT values in non-Hispanic Asians were highest among children (58% compared to non-Hispanic black children) and lowest among men (12% compared to Mexican-American men). Covariate-adjusted totalT values in men were higher at age 55–60 years compared to ages 35 and 80 years, a pattern different from that observed in previous NHANES cycles. CONCLUSIONS: TotalT patterns were different among age groups in men compared with previous NHANES cycles. Covariate-adjusted totalT values peaked at age 55–60 years in men, which appeared to be consistent with the increased use of exogenous testosterone. Differences among race/ethnic groups existed and appeared more pronounced in children than adults.